Peningkatan Kesehatan Kader Keluarga Melalui Pengelolaan Penyakit Diabetes Mellitus di Wilayah Kerja Puskesmas Sitopeng - Badriah, Badriah; SESARIA, TIFANNY; Hidayat, Eyet; Komarudin, Komarudin; Yahya, Syarif Zen; Zaitun, Zaitun; Sriyatin, Sriyatin (PASAI : Jurnal Pengabdian kepada Masyarakat, 2025)
Background: Diabetes Mellitus type 2 (DM T2) is one of the main focuses of NCDs in Indonesia with an increasing prevalence rate. DM management requires a multidisciplinary approach and family support that involves medical, psychological, and social aspects. Objective: This community service program aims to improve the knowledge, skills, and independence of family and community cadres in the prevention and management of T2 DM through a multidisciplinary approach to nursing. Method: The activity will be carried out in August 2025 at RW 05 Argasunya Village, Cirebon City. Methods include health screenings, education, psychosocial counseling, and self-care training. Participants consisted of Non-Communicable Disease (NCD) cadres, at-risk individuals, pregnant women, children, the elderly, and families of sufferers. Results: There was an increase in public knowledge about early symptoms, prevention of complications, and self-care skills. Multidisciplinary approaches have proven to be effective in increasing public participation and awareness. Conclusion: This program can be used as a model of community intervention for comprehensive management of T2 DM.